Analisis Kriminologi Tindak Pidana Pencurian Arus Listrik Oleh Pihak Keluarga (Studi Kasus Di Desa Mandeu Kecamatan Raimanuk Kabupaten Belu) - Alfes, Maria Madalena; Pello, Jimmy; Dede, Ngongo (Law Faculty, Nusa Cendana University, 2025)
The research titled Criminological Analysis of the Crime of Electric Current Theft by the Family was conducted in Mandeu Village, Raimanuk District, Belu Regency. This study aimed to identify the causes of electricity theft by households and efforts to prevent and address it in Mandeu Village. The research method is observational, an empirical study to understand theories about the occurrence process and the workings of law in society. It is also descriptive-analytical, providing a clear and comprehensive picture of electricity theft by customers of PT PLN (Persero) Sub-Branch Halilulik and prevention efforts. The results show that perpetrators of electricity theft could be charged under Article 362 of the Criminal Code on theft. However, due to the existence of a specific law, Article 19 of Law No. 15 of 1985, updated by Law No. 30 of 2009 regulating electricity, it is more appropriate to apply the special rule, in line with the legal principle of lex specialis derogat legi generalis . Electricity theft in Mandeu Village is caused by several factors, including economic constraints, lack of legal awareness, and limited access to electricity. Prevention efforts include community education and stricter monitoring by authorities. In resolving cases, electricity theft is often not reported or taken to court but settled amicably at the scene to avoid conflicts between customers and P2TL officers. This approach aims to maintain social harmony while addressing the issue effectively.